Pediatric antibiotic stewardship programs in Europe: a pilot survey among delegates of The European Academy of Pediatrics - Reingold, Stephen M.; Grossman, Zachi; Hadjipanayis, Adamos; Del Torso, Stefano; Valiulis, Arunas; Dembinski, Lukasz; Ashkenazi, Shai (Frontiers in Pediatrics, 2023)
Background Antibiotic resistance of bacteria is one of the leading causes of morbidity and mortality worldwide. Efforts to endorse judicious antibiotic use and contain its resistance have become a priority of the WHO and other leading medical organizations worldwide. One proven practice in this regard is the establishment of pediatric antibiotic stewardship programs (ASPs), which are recommended widely. The aim of this study was to survey the current situation of pediatric ASPs in European countries and establish a database for future attempts to harmonize pediatric ASPs and antibiotic use in Europe. Methods A web-based survey was conducted among national delegates of the European Academy of Pediatrics. The survey assessed the presence of pediatric ASPs in the representative’s countries in the inpatient and outpatient settings, the staff included in the programs and their details activities regarding antibiotic use. Results Of the 41 country delegates surveyed, 27 (66%) responded. In-patient pediatric ASPs were reported in 74% (20/27) countries, and out-patient programs for 48% (13/27), with a considerable variability in their composition and activities. Guidelines for pediatric infectious syndromes were established in nearly all countries (96%), with those for neonatal infections (96%), pneumonia (93%), urinary tract (89%), peri-operative (82%), and soft tissue (70%) infections being the most common. Pediatric ASPs were reported at the national (63%), institutional (41%) and regional/local (<15%) levels. Pediatricians with infectious disease training (62%) and microbiologists (58%) were the most common members of the program’s personnel, followed by physician leaders (46%), infectious disease/infection control physician (39%), pharmacist (31%) and medical director representatives (15%). Activities of the pediatric ASPs included education (85%), monitoring and reporting of antibiotic use (70%) and of antibiotic resistance (67%), periodic audits with feedback (44%), prior approval (44%) and post-prescription review of selected antibiotic agents (33%). Conclusion Although pediatric ASPs exist in most European countries, hierarchy, components and activities of the programs vary considerably. Initiatives to harmonize comprehensive pediatric ASPs across the European continent as a major pillar of coordinated efforts to reduce antibiotic resistance are needed.